Desain Lintasan Belajar dengan Menggunakan Problem Based Learning pada Materi Luas Permukaan dan Volume Prisma - Mariana Marta Towe (Universitas Serang Raya, 2023)
This type of research is design research, namely research that focuses on developing theories and learning activities. This research aims to design a learning trajectory on the surface area and volume of prism using PBL and its applicationin learning using PBL. The research was carried out at SMP Negeri 2 Larantuka in 2023 on 12 students in class VIIIb and was 16 students in class VIIIa. This research was carried out in accordance with the stages proposed by Gravemeijer & Cobb, namely the preparation stage (preparing for the experiment), the research stage (design experiment) and the retrospective analysis. The result obtained are that the design of a learning trajectory for surface area and prism volume material using the PBL model is theoretically able to facilitate the discorvery of the concepts of surface area and prism volume for class VIII SMP students. The learning process also contains PBL steps, namely orientation, organization, guiding individual and group investigations, developing and presenting work result, analysis and evaluating. Keywords: Learning Trajectory, Problem Based Learning, Prism